A Survey of Users of Corporate Planning Models - Naylor, Thomas H.; Schauland, Horst (Management Science, 1976)
Why are over 2,000 corporations either using, developing, or planning to develop some form of corporate simulation model? What types of companies are using corporate planning models? How are they being used? Which resources are required? These are among the questions which were raised in a recent survey of 346 companies whose results are summarized in this paper. The paper also examines the costs and benefits to be derived from using corporate simulation models. Finally, drawing on the survey results, the authors speculate on future developments in the field of corporate modeling.